Patient characteristics associated with hospitalisations for ambulatory care sensitive conditions in Victoria, Australia - Ansari Zahid; Haider Syed Imran; Ansari Humaira; de Gooyer Tanyth; Sindall Colin (BMC, 2012)
Abstract Background Ambulatory Care Sensitive Conditions (ACSCs) are those for which hospitalisation is thought to be avoidable with the application of preventive care and early disease management, usually delivered in a primary care setting. ACSCs are used extensively as indicators of accessibility and effectiveness of primary health care. We examined the association between patient characteristics and hospitalisation for ACSCs in the adult and paediatric population in Victoria, Australia, 2003/04. Methods Hospital admissions data were merged with two area-level socioeconomic indexes: Index of Socio-Economic Disadvantage (IRSED) and Accessibility/Remoteness Index of Australia (ARIA). Univariate and multiple logistic regressions were performed for both adult (age 18+ years) and paediatric (age <18 years) groups, reporting odds ratios (OR) and 95% confidence intervals (CI) for a number of predictors of ACSCs admissions compared to non-ACSCs admissions. Results Predictors were much more strongly associated with ACSCs admissions compared to non-ACSCs admissions in the adult group than for the paediatric group with the exception of rurality. Significant adjusted ORs in the adult group were 1.06, 1.15, 1.13, 1.06 and 1.11 for sex, rurality, age, IRSED and ARIA variables, and 1.34, 1.04 and 1.09 in the paediatric group for rurality, IRSED and ARIA, respectively. Conclusions Disadvantaged paediatric and adult population experience more need of hospital care for ACSCs. Access barriers to primary care are plausible causes for the observed disparities. Understanding the characteristics of individuals experiencing access barriers to primary care will be useful for developing targeted interventions meeting the unique ambulatory needs of the population.